Formación de anillos de crecimiento por estrés hídrico y defoliación en Juglans neotropica Diels y Podocarpus oleifolius D. Don. bajo condiciones controladas en la ciudad de Loja - Ordóñez González, Deysy Laura (2024)
The study of tree-rings allows us to understand how natural and anthropogenic factors influence during the tree growth, acting as indicators of stress suffered during their development. This study aimed to evaluate the formation of tree-rings due to water stress and defoliation in Juglans neotropica Diels y Podocarpus oleifolius D. Don. under controlled conditions in Loja city. For this purpose, three treatments were established: T0 (control), T1 (immediate defoliation) and T2 (defoliation by water stress), distributed in two physical media (polyethylene bags and direct soil) with 20 replications per treatment on Juglans neotropica and 18 on Podocarpus oleifolius. At the beginning of the experiment, a vertical incision was made in the stem of all individuals to create a scar in the xylem as a reference point. The diameter was measured biweekly and transverse anatomic section were made at the base of the stem to analyze the formation of tree- rings. The rings were identified and delimited with the ICY software. The biweekly increase of the diameter was analyzed and visualized with the statistical program R, to compare the development of the species under study with the points of water stress and defoliation in each treatment. The results showed a higher number of rings in the polyethylene bags than in direct soil for both species. The formation of complete rings was clearly related with the periods of defoliation, while the periods of water stress from four to eight weeks did not influence the formation of tree-rings. Reaction rings were evidenced only in the controls and incomplete rings were associated with a deterioration in their individual phytosanitary status. Therefore, defoliation is the main factor for the formation of complete tree-rings, generating three to six bands of flattened cells. Expanding this type of study to new species is vital for a better understanding of the adaptation of tropical species to extreme climatic variations and to measure their level of resilience.